Nanotechnologia – perspektywy i osiągnięcia w badaniach i konserwacji dzieł sztuki - Rogal, Robert; Żychska, Anna (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2014)
Nanotechnology – perspectives and achievements in research and conservation of the works of art This paper is an overview discussing nanotechnology as a dynamically develop ing interdisciplinary fild, offering in recent years new tools and materials also for conservation of the works of art. The origin and defiitions of nanotechnolo gy and nanomaterials are presented as well as classifiation of nanoobjects along with examples and signifiance of the presence of nanostructures in the nature and in historical artworks. The role of microscopy in studying and designing nao structures is underlined. The processes of manufacturing nanomaterials with „topdown” and „bottom-up” methods are characterised. Some examples of employing nanostructures in conservation of the works of art are presented, such as Rusing silicone microemulsions for hydrofobisation of stone materials, using fitering and magnetic gels for cleaning of paintings, using nanoparticulate TiO2 for manufac turing self-cleaning facade paints or using nanolime for deacidifiation of paper and canvas and for consolidation of mineral supports and paint layers. Readers’ attention is drawn to the possibility of incorporating nanoparticles into other materials and partial modifiation of their properties. The results of microscop ic analysis of the Nanorestore lime are presented. They have revealed, that nan oparticles of that material quickly accumulate into aggregates and agglomerates, which results in loosing the properties of a nanomaterial. The present achieve ments of nanotechnology in the fild of research and conservation of the Works of art are evaluated, the perspectives are drawn and the directions of further ex - pected research are indicated.